1986
DOI: 10.1002/ajpa.1330690402
|View full text |Cite
|
Sign up to set email alerts
|

Age determination of the male Os pubis

Abstract: An extensive (n = 739) sample of well-documented male pubic bones was examined for age-related features. Using the traditional aging methods, Todd's system was found to over-age and both the Todd and the McKern-Stewart systems did not account for age variability seen in advanced pubic bone patterns. Based on a 5-year interobserver error study, certain categories in each system were collapsed because observers could not consistently differentiate between them by morphological pattern. The traditional and the mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
158
1
10

Year Published

1996
1996
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 275 publications
(174 citation statements)
references
References 10 publications
5
158
1
10
Order By: Relevance
“…Todd subsequently expanded his methodology to white females and black males and females (Todd, 1921a,b,c). More recently, Katz and Suchey (1986) refined the Todd phase method using a sample of modern autopsied remains from the Los Angeles County Coroner's Office. These authors concluded that the sex-and population-based differences had a marked impact on the reliability of the method.…”
Section: Introductionmentioning
confidence: 99%
“…Todd subsequently expanded his methodology to white females and black males and females (Todd, 1921a,b,c). More recently, Katz and Suchey (1986) refined the Todd phase method using a sample of modern autopsied remains from the Los Angeles County Coroner's Office. These authors concluded that the sex-and population-based differences had a marked impact on the reliability of the method.…”
Section: Introductionmentioning
confidence: 99%
“…Todd later expanded the method to include white females and black males and females [15][16][17]. More recently, Katz and Suchey [18], refined the Todd phase method using a sample of modern autopsied remains from the Los Angeles County Coroner's Office. They concluded that sex-and population-based differences have a considerable impact on the reliability of the method.…”
Section: Introductionmentioning
confidence: 99%
“…When methods based on, for example, the pubic symphysis [51][52][53][54][55][56] and auricular surface [57][58][59][60][61] are considered, it is clear that their mean errors are also high. It seems that age estimation in adults still remains challenging, and that the Lamendin and modified Lamendin techniques are probably on par with other methods used in adult age estimation.…”
Section: Discussionmentioning
confidence: 99%